Analysis of the employment status of Iranian public universities graduates and the governmental policy using system dynamics approach. (January 2023) - Shahsavari-Pour, Nasser; Darabi, Leila; Zaer-Miri, Setareh
The increasing young population of Iran and the subsequent increase in the unemployment rate in recent years make the government adopt temporary policies to solve the unemployment problem. Establishing private universities and increasing the capacity of university admissions in higher education are among these policies. Although these policies can reduce the youth unemployment problem temporarily, it leads to an influx of highly educated people in the labor market in the long term. Creating job opportunities for these young people will be more difficult, which requires the extensive cooperation of universities and higher education institutions to train student entrepreneurs. Hence, in this present study, the employment of university graduates is simulated through system dynamics approach. Then using the experimental design method, sensitivity analysis and optimization of variables are performed. In the following, identifying the variables influencing the employment of university graduates, scenarios are introduced regarding dynamic universities in youth employment.